Installation art: therapeutic experience of grief and loss / Rozidalina Abdullah - Abdullah, Rozidalina (2010)
Collecting junks or abandoned materials around the house will benefit us in many important aspects. The strength and quality of the materials can be critically judged when it turns to be an artwork. This Project-Based Research enables the researcher to implement her ideas with the underlying theme of ‘the lost memories'. It is an introduction of innovative art experience and the essence of the installation art entitled The Remedy to My Sadness’. The developmental practices focused on the exploration of personal narrative and creative processes involving experimentation of media and materials. The installation art is dynamic, reflective and connected to contemporary studies. Step-by step process and guidelines in producing an installation art using glass bottles were provided particularly to promote clearer understanding. Suggestion of suitable media and materials encouraged the viewers to produce art, based on individual’s creativity. The research also suggests personal dialogic experience and conflicting memories to engage the process of producing art as a therapeutic experience. Further research is implied for the development of educational artistry through experiences with art.